Ecology of female mating failure/lifelong virginity: a review of causal mechanisms in insects and arachnids. Issue 1 (5th February 2019) - Rhainds, Marc
Abstract: Sexual reproduction implies binary outcomes of competitive interactions for access to male gametes: lifelong virgin females with null fitness vs. mated females with variable (generally nonzero) fitness. Female mating failure has long remained a dormant concept in sexual selection theory in part because it is acutely maladaptive (lifelong virgins that do not reproduce are strongly selected against) and also due to widespread acceptance of the Bateman–Trivers paradigm (anisogamy and correlated sex roles). Based on recent scientific output on lifelong virginity across multiple taxonomic groups in insects (Coleoptera, Diptera, Hemiptera, Lepidoptera, Odonata, Orthoptera, Strepsiptera), female mating failure has become a mainstay of sexual selection over the last decade. Lifelong virginity and senescence (death) are intertwined processes; old virgin females compensate for increased risk of lifelong virginity by becoming less choosy and increasing investment in mating‐related activities. Low rates of female lifelong virginity (<5%) in most natural populations of insects indicate that sex generally 'works' due to selective pressures acting on both males and females to enhance lifetime fitness. Mating failures are most common in insects with female flightlessness; these pressures may lead in evolutionary time to transitionary pathways from sexual reproduction to parthenogenesis. Female mating probability is affected by nonlinear density‐dependent processes dependent upon the scale of observation (mate‐encounter Allee effect at large spatial scales, mating interferences between females at small scales). Mate choice and sex role reversal (females being the active sexual partner) are ubiquitous in insects and arachnids with significant paternal investment, but consequences in terms of female lifelong virginity remain unknown. Logistically, conceptual development of female mating failure in insects is most limited by the lack of broadly applicable methods to assess rates of lifetime virginity among flighted females. Abstract : The review focuses on causal mechanisms associated with female mating failure (FMF, or lifelong virginity) in insects and arachnids. Attributes of females associated with a relatively high risk of FMF include low mobility, small body size, old age, short lifespan, long prereproductive maturation, physical location of mate‐seeking females, and discriminatory mating behavior. Demographic variables linked with a high risk of FMF include emergence time (reproductive asynchrony, male‐biased sex ratio, and both very low and high population densities).